Pre-eclampsia and risk of later kidney disease: nationwide cohort study. (29th April 2019) - Kristensen, Jonas H; Basit, Saima; Wohlfahrt, Jan; Damholt, Mette Brimnes; Boyd, Heather A
ABSTRACT: Objective: To investigate associations between pre-eclampsia and later risk of kidney disease. Design: Nationwide register based cohort study. Setting: Denmark. Population: All women with at least one pregnancy lasting at least 20 weeks between 1978 and 2015. Main outcome measure: Hazard ratios comparing rates of kidney disease between women with and without a history of pre-eclampsia, stratified by gestational age at delivery and estimated using Cox regression. Results: The cohort consisted of 1 072 330 women followed for 19 994 470 person years (average 18.6 years/woman). Compared with women with no previous pre-eclampsia, those with a history of pre-eclampsia were more likely to develop chronic renal conditions: hazard ratio 3.93 (95% confidence interval 2.90 to 5.33, for early preterm pre-eclampsia (delivery <34 weeks); 2.81 (2.13 to 3.71) for late preterm pre-eclampsia (delivery 34-36 weeks); 2.27 (2.02 to 2.55) for term pre-eclampsia (delivery ≥37 weeks). In particular, strong associations were observed for chronic kidney disease, hypertensive kidney disease, and glomerular/proteinuric disease. Adjustment for cardiovascular disease and hypertension only partially attenuated the observed associations. Stratifying the analyses on time since pregnancy showed that associations between pre-eclampsia and chronic kidney disease and glomerular/proteinuric disease were much stronger within five years of the latest pregnancy (hazard ratio 6.11 (3.84 to 9.72) and 4.77 (3.88 to 5.86), respectively) than five years or longer after the latest pregnancy (2.06 (1.69 to 2.50) and 1.50 (1.19 to 1.88). By contrast, associations between pre-eclampsia and acute renal conditions were modest. Conclusion: s Pre-eclampsia, particularly early preterm pre-eclampsia, was strongly associated with several chronic renal disorders later in life. More research is needed to determine which women are most likely to develop kidney disease after pre-eclampsia, what mechanisms underlie the association, and what clinical follow-up and interventions (and in what timeframe post-pregnancy) would be most appropriate and effective.